Major aspects of chinese religion and philosophy dao of inner saint and outer king - Shan, Chun (Springer Berlin Heidelberg, 2012)
This book does not only explore the innate relations between confucianism, daoism and buddhism since their origins till its recent developments. By relating the three major traditions of chinese philosophy he also attempts to concentrate the new-confucianism on its unified origins and substantial implications by applying its inherent endeavour to relate and unite all spheres: these topics being the intimate relations between religion and philosophy, their inner and outer way (including the correlation between confucian and daoist legacies) as well as the unity between cosmos (heaven), country, state, society and family. Masterful introduction to traditional chinese ways of thinking, embodied in the “three teachings” of confucianism, daoism, and buddhism. A valuable resource for those seeking a deeper understanding of Chinese philosophy and religion, that will satisfy both the curious non-specialist and the seasoned scholar in its treatment of a highly pertinent topic to the future of China, and not only its past. A very revealing view of how a learned, serious chinese intellectual understands the diverse riches to be found in the chinese tradition. Attempting to cover virtually all of the chinese philosophical and religious traditions and relate them to western ideas, willing to pursue normative conclusions and discuss their applicability to modern life. Preface -- Part one - Inner saint: some aspects of chinese religion -- 1. Chinese faith triangle: confucianism, daoism and buddhism -- 2. The basic spirit of chinese culture and national faith -- 3. The definition of religion -- 4. A hermeneutic investigation into heaven: the key concept of chinese faith system -- 5. The religious commitment of confucian style -- 6. Religious aspects of daoism -- 7. The Buddha nature theory and it’s social value -- 8. Human dignity reflected in confucianism and daoism -- 9. A confucian perspective on the enlightenment and religion -- Part two - Outer king: some aspects of chinese philosophy -- 10. The spirit of chinese philosophy -- 11. A brief introduction to the new history of chinese philosophy -- 12. Daoism as philosophy of Lao Zi -- 13. Zhuang Zi’s mentality of cosmic liberty -- 14. The philosophical aspects of chinese buddhism -- 15.Chinese cosmopolitanism (tianxia) -- 16. Moral happiness of Confucius and Yan Hui (Kong Yan Le chu) -- 17. Proprieties as governmental rules of confucian hermeneutics -- 18. Moral rights and justification of revolution: heart-nature theme of Mencius -- 19. Political personality revealed in the great learning (daxue) -- 20. Natural justice and its political implications in the doctrine of the mean (zhongyong) -- Bibliography -- Index.